The role of antioxidants in the treatment of vitiligo - Beata Skibska; Anna Gorąca; Katarzyna Bujnicka (Polish Pharmaceutical Society, 2021)
Melanogenesis is a multi-stage process of melanin synthesis. Melanogenesis depends on many factors, both endogenous (e.g. hormones) and exogenous (e.g. synthetic and plant drugs). Melanin in humans is responsible for the color of the skin, hair and iris of the eye. Melanin is synthesized in melanocytes inside specialized organelles - melanosomes. Its synthesis involves signaling pathways such as: cAMP (cyclic adenosine monophosphate), Wnt (Wnt signaling is activated by highly conserved Wnt proteins that are secreted as palmitoylated glycoproteins) or catenin-dependent signaling, ERK/MAPK (mitogen-activated protein kinases/extracellular signal-regulated kinases), NO/cGMP/PKG. The main enzyme involved in the synthesis of melanin is tyrosinase. The activity of tyrosinase is influenced by many factors, including: ultraviolet radiation, cytokines, hormones, as well as temperature and pH. This enzyme causes the oxidation of tyrosine, which is a substrate in melanin biosynthesis. Melanocytes produce different types of melanin; brown-black or dark eumelanin, which is insoluble and has photoprotective properties, and red-yellow pheomelanin, which can generate hydroxyl radicals and peroxide anion when exposed to ultraviolet rays. Loss of melanocytes or their destruction contributes to the development of vitiligo. It is characterized by clearly defined, discolored patches of various shapes and sizes. About 2% of the population suffer from this disease. Vitiligo can cause negative psychosocial effects and reduce patients' quality of life. People with vitiligo may also develop depressive symptoms. Antioxidants have proved to be helpful in the treatment of vitiligo. Lipoic acid together with corticosteroids and NB-UVB (narrowband ultraviolet B) and completely trans-retinoic acid accelerate the re-pigmentation of the skin in non-segmental progressive vitiligo. A beneficial effect in vitiligo was also observed when administering vitamin D, vitamin B 12, vitamin C, polyphenols or Gingko biloba extracts. The aim of the study is to demonstrate the positive effect of antioxidants in the treatment of vitiligo.